The Impact of Interpretive Messaging and Animal Handling on Visitors' Perceptions of Animal Welfare and Empathic Reactions. Issue 1 (April 2021) - Minarchek, Matthew J.; Skibins, Jeffrey C.; Luebke, Jerry F.
Zoos are increasingly turning to ambassador animal programs to address animal welfare issues and visitors' empathic responses. However, little is known, if or how, animal handling practices and interpretation impact attendees' perceptions of animal welfare and/or empathy. To evaluate these effects, eight ambassador animal program videos were created employing varying combinations of animal handling (traditional/free choice), interpretive messaging (traditional/empathy-based), and choice and control language (present/absent). Online questionnaires ( N  = 1, 185) were used to assess participants' environmental and empathic predispositions before viewing and perceptions of animal welfare and empathic reactions immediately after viewing a video. Results revealed that empathic reactions were moderately correlated with perceptions of animal welfare ( r  = .53, p  < .001) and mean empathic responses were higher for free choice handling and empathic messaging videos versus traditional handling and messaging. Programming recommendations are discussed that can improve visitors' perceptions of animal care and elicit strong empathic reactions.